mplementation of Differentiated Instruction in Planning, Teaching, and Assessing EFL in the Independent Curriculum - Hamzah, Ikhlasul; Sunra, La; Halim, Abdul; Tahir, M.; Korompot, Chairil Anwar; Djirong, Agussalim (Universitas Negeri Makassar, 2025)
Abstract. This study aims to explore the implementation of Differentiated Instruction (DI) in the planning, implementation, and evaluation of English language (EFL) learning in the Independent Curriculum at SMK Negeri 4 Makassar. A qualitative approach with a case study design was used to explore the perceptions of six teachers and six students through interviews, observations, and documentation. The results showed that learning planning was not fully based on student profiles. Teachers used uniform lesson plans without differentiation of content, process, or product. DI implementation was carried out in a limited and situational manner, such as student grouping or peer tutoring assistance, but was not yet structured. Evaluation was still predominantly summative, without initial or formative assessments that could direct differentiation strategies. Teachers understood DI intuitively, but did not yet have a strong theoretical basis. Students expressed the need for more varied learning methods, according to their interests and learning styles. The main obstacles in implementing DI were time constraints, a large number of students, and minimal training. This study recommends teacher training in differentiation planning and formative assessment integration to support more adaptive and inclusive learning. Keywords: Differentiated Instruction, Merdeka Curriculum, Lesson Planning, Learning Evaluation, EFL